A wideband graphene coated dielectric resonator antenna with circular polarization generation technique for THz applications. (February 2021) - Gotra, Shailza; Pandey, V.S.; Yaduvanshi, R.S.
Abstract: A circular polarization generation technique is implemented in the rectangular dielectric resonator antenna (DRA) using graphene material. A partial coating of graphene material on the faces of DR is being used instead of the conventional metallic coating for obtaining the circularly polarized response. This coating acts like the electric wall is arranged in orthogonal fashion on the faces of DR. It generates the orthogonal degenerate modes inside the DR which is amenable for the generation of circular polarization. The proposed antenna provides a wide 10-dB impedance bandwidth of 48.86% and 7.06% of overlapped 3-dB axial-ratio (AR) bandwidth. The wideband response is obtained due to the merging of higher-order modes inside the rectangular DR. Furthermore, the AR bandwidth can be tuned at different frequencies within the operating passband by varying the arrangement of orthogonal coating. Highlights: This paper presents a silicon-based DRA using graphene coating provides circular polarization generation technique. The orthohonal coating arrangement provides the rotation of field vectors inside DR. The proposed antenna provides a wide -10 dB impedance bandwidth of 48.86% and 7.06% of overlapped 3 dB AR bandwidth. The wideband response is obtained due to the merging of higher-order modes inside the rectangular DR. The AR bandwidth can be tuned at different frequencies by varying the arrangement of orthogonal coating.